The limits to transforming the environment and the limits to sociological knowledge - Schroeder, R (Molecular Diversity Preservation International (MDPI), 2010)
This paper argues that the social sciences are fragmented in addressing the environmental challenge of increasing resource depletion. To address this problem, the paper puts forward a framework which encompasses several disciplinary approaches, and above all a long-term historical perspective and a realist sociology of science and technology which, in combination, provide a means of understanding the disruptive changes in the transformation of the environment. The paper then focuses on energy and gives an overview of the various social forces that can potentially counteract the future tensions arising from the foreseeable depletion of energy sources. It argues that only some of these countervailing forces—namely state intervention and technological innovation—provide viable potential solutions to these tensions. However, these solutions themselves face severe constraints. The paper concludes by arguing that a realistic assessment of constraints is the most useful, though limited, service that social science can contribute to our understanding of the relation between social and environmental transformation.